(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article presents comments on a special type of artistic means, periphrasis. The views of foreign scientists on the theory of periphrasis are taken into account. The types of periphrasis in the work of the poet I. Yusupov and its poetic image, emotional-expressive service are discussed.